2022
DOI: 10.3389/fcell.2022.834815
|View full text |Cite
|
Sign up to set email alerts
|

Tgfbr2 in Dental Pulp Cells Guides Neurite Outgrowth in Developing Teeth

Abstract: Transforming growth factor β (TGFβ) plays an important role in tooth morphogenesis and mineralization. During postnatal development, the dental pulp (DP) mesenchyme secretes neurotrophic factors that guide trigeminal nerve fibers into and throughout the DP. This process is tightly linked with dentin formation and mineralization. Our laboratory established a mouse model in which Tgfbr2 was conditionally deleted in DP mesenchyme using an Osterix promoter-driven Cre recombinase (Tgfbr2cko). These mice survived po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 122 publications
(219 reference statements)
0
20
0
Order By: Relevance
“…We previously reported that Tgfbr2 in dental pulp fibroblasts and odontoblasts regulates the postnatal neuro-pulpal development of mouse molars [3,7,9]. A shallow dentin injury without pulp exposure has been shown to initiate the expression of neurotrophic factors, such as nerve growth factors (NGF), by odontoblasts [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously reported that Tgfbr2 in dental pulp fibroblasts and odontoblasts regulates the postnatal neuro-pulpal development of mouse molars [3,7,9]. A shallow dentin injury without pulp exposure has been shown to initiate the expression of neurotrophic factors, such as nerve growth factors (NGF), by odontoblasts [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…In this report, we sought to determine whether the signaling downstream of Tgfbr2 in the developing dental pulp mesenchyme also regulates reactionary dentinogenesis and odontoblast secretion of neurotrophic signals that promote axon sprouting. Since conditional deletion of Tgfbr2 in the Osteocalcin-Cre model results in pulpal obliteration [5], and deletion in the Osterix-Cre model results in late postnatal death [3,[7][8][9], we utilized the tetracycline-responsive element in the Osterix-Cre mouse model to isolate conditional deletion of Tgfbr2 to the time period immediately before the dentin injury through the studies on the injury response. Our ISH of Sp7 indicated that there was Tgfb2 deletion in the dental pulp, confirming the validity of our model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations